Evolution of the vertebrate bone matrix: An expression analysis of the network forming collagen paralogues in amphibian osteoblasts. Issue 6 (15th May 2013) - Aldea, Daniel; Hanna, Patricia; Munoz, David; Espinoza, Javier; Torrejon, Marcela; Sachs, Laurent; Buisine, Nicolas; Oulion, Silvan; Escriva, Hector; Marcellini, Sylvain
ABSTRACT The emergence of vertebrates is closely associated to the evolution of mineralized bone tissue. However, the molecular basis underlying the origin and subsequent diversification of the skeletal mineralized matrix is still poorly understood. One efficient way to tackle this issue is to compare the expression, between vertebrate species, of osteoblastic genes coding for bone matrix proteins. In this work, we have focused on the evolution of the network forming collagen family which contains the Col8a1, Col8a2, and Col10a1 genes. Both phylogeny and synteny reveal that these three paralogues are vertebrate‐specific and derive from two independent duplications in the vertebrate lineage. To shed light on the evolution of this family, we have analyzed the osteoblastic expression of the network forming collagens in endochondral and intramembraneous skeletal elements of the amphibian Xenopus tropicalis. Remarkably, we find that amphibian osteoblasts express Col10a1, a gene strongly expressed in osteoblasts in actinopterygians but not in amniotes. In addition, while Col8a1 is known to be robustly expressed in mammalian osteoblasts, the expression levels of its amphibian orthologue are dramatically reduced. Our work reveals that while a skeletal expression of network forming collagen members is widespread throughout vertebrates, osteoblasts from divergent vertebrate lineages express different combinations of network forming collagen paralogues. J. Exp. Zool. (Mol. Dev. Evol.) 320B: 375–384, 2013. © 2013 Wiley Periodicals, Inc.